2012
DOI: 10.1111/j.1740-8784.2011.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Building a Knowledge-Driven Society: Scholar Participation and Governance in Large Public Works Projects

Abstract: Previous studies have found no relationship between scholar participation and public project performance. Building on the work of Lindblom (1977; 1990), I propose a model depicting scholars' roles in social organizations and governance. A study of thirty‐two cases of large public works projects in China and seventeen projects in thirteen other countries shows a moderately positive relationship. The study further shows the greatest influence on project success occurs when participating scholars serve as informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Bush, 1987;Hayek, 1960;Scott, 1995) have argued that institutions or orders are bearers or carriers of dispersed knowledge, values and culture in society. The important role of knowledge and scholars in institutional change has also been emphasized in many previous studies (Hayek, 1945;North, 1990;Veblen, 1904;Yang, 2009Yang, , 2010aYang, , 2010bYang, , 2012Yang and Wu, 2012). Ruttan et al (Ruttan, 1978, 1984Ruttan and Hayami, 1984) stressed the importance of technical change and social science knowledge in induced institutional change.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Bush, 1987;Hayek, 1960;Scott, 1995) have argued that institutions or orders are bearers or carriers of dispersed knowledge, values and culture in society. The important role of knowledge and scholars in institutional change has also been emphasized in many previous studies (Hayek, 1945;North, 1990;Veblen, 1904;Yang, 2009Yang, , 2010aYang, , 2010bYang, , 2012Yang and Wu, 2012). Ruttan et al (Ruttan, 1978, 1984Ruttan and Hayami, 1984) stressed the importance of technical change and social science knowledge in induced institutional change.…”
Section: Discussionmentioning
confidence: 87%
“…Many studies have indicated that it is not only possible but also useful to identify a set of necessary design principles or core elements for the study of institutional arrangements and changes (Lindblom, , ; Ostrom, ; Yang, , ; Yang and Wu, , ; Yang, ). From the perspective of the science and technology used, participants, and rules influenced, we determined nine working principles to explain the success of some science‐driven institutional changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yang's () article, ‘Building a knowledge‐driven society: Scholar participation and governance in large public works projects’, uses forty‐nine cases (thirty‐two from China and seventeen from other countries) to study the impact of scholars' participation. He found that scholars' participation is more effective when the projects are at the grassroots level or there is low political intervention.…”
Section: The Papers In This Special Issuementioning
confidence: 99%